The Difference in Facial Movement Between the Medial and the Lateral Midface: A 3-Dimensional Skin Surface Vector Analysis. (30th March 2021) - Freytag, David L; Alfertshofer, Michael G; Frank, Konstantin; Melnikov, Dmitry V; Moellhoff, Nicholas; Swift, Arthur; Heisinger, Stephan; Gotkin, Robert H; Ehrl, Denis; Cotofana, Sebastian
Abstract: Background: Our understanding of the functional anatomy of the face is constantly improving. To date, it is unclear whether the anatomic location of the line of ligaments has any functional importance during normal facial movements such as smiling. Objectives: The authors sought to identify differences in facial movements between the medial and lateral midface by means of skin vector displacement analyses derived from 3-dimensional (3D) imaging and to further ascertain whether the line of ligaments has both a structural and functional significance in these movements. Methods: The study sample consisted of 21 healthy volunteers (9 females and 12 males) of Caucasian ethnic background with a mean age of 30.6 (8.3) years and mean BMI of 22.57 (2.5) kg/m 2 . 3D images of the volunteers' faces in repose and during smiling (Duchenne type) were taken. 3D imaging-based skin vector displacement analyses were conducted. Results: The mean horizontal skin displacement was 0.08 (2.0) mm in the medial midface (lateral movement) and was −0.08 (1.96) mm in the lateral midface (medial movement) ( P  = 0.711). The mean vertical skin displacement (cranial movement of skin toward the forehead/temple) was 6.68 (2.4) mm in the medial midface, whereas it was 5.20 (2.07) mm in the lateral midface ( P  = 0.003). Conclusions: The results of this study provide objective evidence for an antagonistic skin movement between the medial and lateral midface. The functional boundary identified by 3D imaging corresponds to the anatomic location of the line of ligaments. Level of Evidence: 4: